Apparatus for exposure of cancer cell lines with extremely low frequency (ELF) alternating magnetic field - Mydlikowski, Remigiusz; Maniak, Krzysztof; Grosman-Dziewiszek, Patrycja; Wiatrak, Benita; Bieńkowski, Paweł; Gębarowski, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper presents the design of a laboratory stand that facilitates the study of the effects of exposure to magnetic induction of extremely low frequency on cultures of cancer cell lines. The designed laboratory bench is adapted to operate in the frequency range of up to 300 Hz and the maximum settable magnetic induction of 2.5 mT. Tests are conducted on cellular test plates of 24, 48, or 96 wells where it is possible to evaluate the combined effect of magnetic field and cisplatin on cancer cells. The conducted tests determined the uniformity of field distribution inside the constructed solenoid establishing the optimal space for cellular research. Preliminary studies of the effect of the magnetic field on the response of cancer cells treated with cisplatin were conducted on the built stand. The study shows that a magnetic field with certain parameters can significantly affect the response of cancer cells to cisplatin treatment. The application of a magnetic field can either promote cell proliferation or, with appropriately selected parameters, lead to increased cytotoxicity. Continued research will allow us to find the appropriate drug concentration parameters when using magnetic field exposure with given parameters.